2013
DOI: 10.1007/s10439-013-0786-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Geometric and Biomechanical Factors in Abdominal Aortic Aneurysm Rupture Risk Assessment

Abstract: The current clinical management of abdominal aortic aneurysm (AAA) disease is based to a great extent on measuring the aneurysm maximum diameter to decide when timely intervention is required. Decades of clinical evidence show that aneurysm diameter is positively associated with the risk of rupture, but other parameters may also play a role in causing or predisposing the AAA to rupture. Geometric factors such as vessel tortuosity, intraluminal thrombus volume, and wall surface area are implicated in the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 98 publications
(145 reference statements)
1
67
0
1
Order By: Relevance
“…There are several studies in the literature comparing FSI and noFSI analyses for single-layered aneurysm models [9,37,38]. Those studies suggested that applying transient pressure uniformly on the lumen sac for the noFSI analysis could be an adequate alternative to FSI analysis for the rupture risk criteria [2]. Khanafer et al [38], in his single-layered axisymmetric AAA model, stated that structural-only analysis, with uniformly applied time-dependent pressure inside the aneurysm lumen, underestimated peak wall stress (PWS) by 8% compared to the FSI analysis at the time of the peak wall stress.…”
Section: Aneurysm Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies in the literature comparing FSI and noFSI analyses for single-layered aneurysm models [9,37,38]. Those studies suggested that applying transient pressure uniformly on the lumen sac for the noFSI analysis could be an adequate alternative to FSI analysis for the rupture risk criteria [2]. Khanafer et al [38], in his single-layered axisymmetric AAA model, stated that structural-only analysis, with uniformly applied time-dependent pressure inside the aneurysm lumen, underestimated peak wall stress (PWS) by 8% compared to the FSI analysis at the time of the peak wall stress.…”
Section: Aneurysm Modelmentioning
confidence: 99%
“…Cerebral artery aneurysms (CAA) and abdominal aortic aneurysms (AAA) are the most common aneurysm types. The AAA arises in the infrarenal aorta with a diameter greater than 3 cm and can be up to 9 cm in length [1,2]. Most of the studies on aneurysms have focused on already existing realistic or idealized aneurysms [33][34][35][36][37][38][39][40][41][42][43] with the aim of defining a relevant rupture criterion [4,7,10,19,20,24].…”
mentioning
confidence: 99%
“…In Fig. 5, a low relative error for wall stress obtained with the coarsest mesh is likely due to the fact that maximum stresses typically occur at highly curved regions, especially ones with a saddle point [29]. Piecewise linear facets cannot accurately model these surface details with coarse mesh sizes.…”
Section: Wall Extrusion Versus Mask Dilation Approachmentioning
confidence: 99%
“…It is often accompanied by the growth of ILT, and ILT formation has been linked to both the progression [1] and risk of rupture [2] of AAA. The mechanisms of ILT formation, as well as the influence of ILT on AAA biomechanics, however, are complex and poorly understood [3,4].…”
Section: Introductionmentioning
confidence: 99%